When to investigate for secondary hyperhidrosis: data from a retrospective cohort of all causes of recurrent sweating. (31st December 2022) - Collercandy, Nived; Thorey, Camille; Diot, Elisabeth; Grammatico-Guillon, Leslie; Thillard, Eve Marie; Bernard, Louis; Maillot, François; Lemaignen, Adrien
Abstract: Background: Identification of underlying diseases is crucial for secondary hyperhidrosis management, but data are lacking to guide appropriate investigation. Objective: To describe aetiologies of recurrent sweating in a hospital setting and the diagnostic performance parameters of their respective clinical/biological features. Patients and Methods: We performed a monocentric evaluative study in a tertiary care centre. Patients with recurrent generalised sweating were selected via the Clinical Data Warehouse (CDW) by screening all electronic hospital documents from the year 2018 using a keyword-based algorithm. All in and out-patients aged ≥ 18 years having reported recurrent sweating for at least 2 weeks in 2018 were included, with a minimum one-year follow-up after symptoms' onset. Results: A total of 420 patients were included. Over 130 different aetiologies were identified; 70 patients (16.7%) remained without diagnosis. Solid organ cancers (14.3% with 13 lung cancers), haematologic malignancies (14.0% with 35 non-Hodgkin's lymphomas) and Infectious Diseases (10.5% including 13 tuberculosis) were the most frequent diagnoses. Other aetiologies were gathered into inflammatory (16.9%) and non-inflammatory (27.6%) conditions. To distinguish non-inflammatory and undiagnosed hyperhidrosis from other causes, fever had a specificity of 94%, impaired general condition a sensitivity of 78%, and C-reactive protein (CRP) > 5.6 mg/l a positive predictive value of 0.86. Symptoms' duration over 1 year was in favour of non-infectious and non-malignant causes (94% specificity). Conclusions: We identified fever, impaired general condition, duration, and CRP as helpful orientation parameters to assess the need for complementary explorations for hyperhidrosis. The study provides a diagnostic algorithm for the investigation of recurrent sweating. KEY MESSAGES: In a hospital setting, malignancies and infections are the most frequently associated diseases, but 1/5 remain without diagnosis. Fever is a specific but not sensitive sign to distinguish inflammatory conditions. Over 1 year duration of symptoms significantly reduce the probability of malignancy or infection as the underlying diagnosis.